Indentation Plastometry of Very Hard Metals. Issue 7 (7th February 2022) - Campbell, Jimmy E; Gaiser-Porter, Marcus; Gu, Wenchen; Ooi, Steve; Burley, Max; Dean, James; Clyne, Trevor William
Abstract : This investigation concerns the application of profilometry‐based indentation plastometry (PIP) to metals with very high hardness, i.e., those with yield stresses of 1.5–3 GPa. The PIP procedure comprises (a) applying a force to an indenter ball, penetrating the sample to a preselected depth, (b) measuring the profile of the indent, and (c) iteratively running a finite element method (FEM) model to obtain the true stress–true strain curve giving optimal agreement between measured and modeled profiles. The procedure is no different when the sample is very hard, although the ball must remain elastic during the process. It is shown that this can be achieved using silicon nitride balls. These can fracture under some conditions, but it is shown that a "proof‐testing" operation can be used to ensure that any particular ball will remain elastic under the complete range of service conditions. It is also shown, via systematic comparisons with the outcomes of uniaxial (tensile and compressive) tests, that reliable stress–strain curves can be obtained for very hard metals. Furthermore, PIP testing has advantages over uniaxial testing for obtaining information about their behavior at relatively high strains (≈15%), as well as being much easier and simpler to implement. Abstract : Profilometry‐based indentation plastometry (PIP) can be successfully applied to very hard metals (yield stress (YS)≈2.5–3 GPa), giving good agreement with uniaxial test outcomes. Requirements for the ball to remain elastic are investigated. PIP allows plasticity characteristics to be established in high strain regimes that cannot be investigated by conventional testing.